Predicting biological invasions in marine habitats through eco‐physiological mechanistic models: a case study with the bivalve Brachidontes pharaonis. Issue 10 (23rd April 2013) - Sarà, G.; Palmeri, V.; Rinaldi, A.; Montalto, V.; Helmuth, B.; Thuiller, Wilfried
Abstract Aim We used a coupled biophysical ecology (BE)‐physiological mechanistic modelling approach based on the Dynamic Energy Budget theory (DEB, Dynamic energy budget theory for metabolic organisation, 2010, Cambridge University Press, Cambridge; DEB) to generate spatially explicit predictions of physiological performance (maximal size and reproductive output) for the invasive mussel, Brachidontes pharaonis. Location We examined 26 sites throughout the central Mediterranean Sea. Methods We ran models under subtidal and intertidal conditions; hourly weather and water temperature data were obtained from the Italian Buoy Network, and monthly CHL‐a data were obtained from satellite imagery. Results Mechanistic analysis of the B. pharaonis fundamental niche shows that subtidal sites in the Central Mediterranean are generally suitable for this invasive bivalve but that intertidal habitats appear to serve as genetic sinks. Main conclusions A BE‐DEB approach enabled an assessment of how the physical environment affects the potential distribution of B. pharaonis. Combined with models of larval dispersal, this approach can provide estimates of the likelihood that an invasive species will become established.